PROBIOTIC APPLICATION IN THE NURSERY AND REARING OF Clarias sp. IN THE TUMPANG SUBDISTRICT - Muhammad Fakhri (Journal of Innovation and Applied Technology, 2017)
The main problem in catfish culture is high mortality and high feed conversion ratio (FCR). The aim of this study was to know the application of probiotic in catfish culture. For nursery, catfish juveniles with size of 2-3 cm was cultivated for 40 days while fish with size of 7-9 cm was cultured for 85 days in grow-out tank. All tanks were administered by probiotic during one culture cycle. Probiotic was directly given to the water and administered by feed. The results showed that survival rates of nursery and grow-out tanks were 95% and 95,8%, respectively. The FCR in the grow-out was 0.76. It can concluded that probiotic application was able to improve the survival rate and the feed conversion ratio in catfish culture.